If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = m + 2 Reorder the terms: 12 = 2 + m Solving 12 = 2 + m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. 12 + -1m = 2 + m + -1m Combine like terms: m + -1m = 0 12 + -1m = 2 + 0 12 + -1m = 2 Add '-12' to each side of the equation. 12 + -12 + -1m = 2 + -12 Combine like terms: 12 + -12 = 0 0 + -1m = 2 + -12 -1m = 2 + -12 Combine like terms: 2 + -12 = -10 -1m = -10 Divide each side by '-1'. m = 10 Simplifying m = 10
| 5(6x+35)+7(x+1)=u | | -2y+10=-2(2y+3) | | x-4=-13 | | 16x^2+y^2-16y=0 | | r+10=15 | | 16x^2+y^2=16y | | -2+x=26 | | 2.1=x-6.1 | | (12)(6)6=x | | 3p=18 | | -10x=70 | | -7x=-168 | | -10.1x=30.3 | | 100(84)=96x | | -10x-20=-190 | | 4x+10x=56 | | 12z=-8 | | -11=x+4 | | 3x^2y+6x^2y^2-144xy^3= | | x^2-3x=-8 | | x=4+-3y | | x^2-18+77= | | 4(2x+-1)=27+3(2x-5) | | x(x+3)=18 | | 38=25+2y | | 7p=6p^2-3 | | v^2-6v+15= | | 0=-16t^2+35t+8 | | 1-5x^2=-3x | | 3(q+4)-10q=2q+3 | | 2x+3x+5=5(2x-3) | | 4z-2(z+6)=7z+8 |